Platelet-mitochondria dual-targeted nanocarriers for enhanced empagliflozin therapy in atherosclerosis - Tang, Yue; Tian, Yue; Wang, Yi; Mei, Xue; Luo, Lijun; Zhang, Fan; Gao, XiaoJin; Wang, Yihua; Hou, Jun; Zhou, Chunyang (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAtherosclerosis (AS) is a primary cause of cardiovascular disease and significantly contributes to the global disease burden. Empagliflozin (EMP), a candidate drug for AS treatment, has not been clinically approved due to challenges including poor solubility, low bioavailability, and potential toxicity.MethodsTo address these challenges, we constructed a platelet membrane-biomimetic, mitochondria-targeted delivery system (PM@EPPT). This system was developed by loading EMP into PCL-PEG polymeric micelle, modifying the PEG terminus with triphenylphosphine (TPP), and coating the nanoparticle surface with platelet membranes. We then evaluated its efficacy against AS using both in vitro and in vivo models.ResultsThe PM@EPPT system exhibited favorable physical properties and biocompatibility. In vitro, it alleviated oxidative stress-induced macrophage apoptosis by scavenging reactive oxygen species (ROS), restoring mitochondrial membrane potential, and activating mitophagy. In ApoE-/- mouse models, PM@EPPT significantly reduced aortic plaque area by 43%, decreased the expression of inflammatory markers (CD68 and MMP-9), increased levels of the plaque stability marker (α-SMA), and improved lipid profiles.DiscussionIn conclusion, PM@EPPT enhances EMP bioavailability through platelet membrane-mediated arterial plaque targeting and TPP-modified mitochondrial targeting. This study provides experimental evidence for optimizing EMP efficacy in AS treatment and developing therapeutic platforms for other poorly soluble drugs targeting AS.